2014
DOI: 10.12691/ajcea-2-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ceramic Waste as Filler in Semi-Dense Bituminous Concrete

Abstract: The purpose of this paper is to evaluate the suitability of ceramic waste as a filler material in Semi-Dense Bituminous Concrete. A bituminous concrete mixes with ceramic dust and hydrated lime were prepared in different proportions (3% and 5%) as filler. The amount of optimum binder content was determined by Marshall Stability test for samples. The mechanical performance was determined for Marshall Stability, deformation behavior or flow, as well as for density and void characteristics base on prevailing Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…For the assessments based on previous studies [16], the amount of ceramic dust and butyl rubber together with the same proportion were prepared with 1%, 2% and 3% by weight of binder to compare with neat binder. The basic processes used to add polymer into bitumen are wet method (addition of solid polymers into asphalt) and dry method (addition of solid polymer into hot mix asphalt or directly to aggregates) [25].…”
Section: Asphalt Mastic Preparation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the assessments based on previous studies [16], the amount of ceramic dust and butyl rubber together with the same proportion were prepared with 1%, 2% and 3% by weight of binder to compare with neat binder. The basic processes used to add polymer into bitumen are wet method (addition of solid polymers into asphalt) and dry method (addition of solid polymer into hot mix asphalt or directly to aggregates) [25].…”
Section: Asphalt Mastic Preparation Methodsmentioning
confidence: 99%
“…In previous studies, ceramics are used as a thermal insulator materials effect on pavement temperature variation [14,15] because of most of pavement distress such as permanent deformation, fatigue cracking and low thermal cracking are highly related to temperature variations. The authors in [16] used ceramic powder and hydrate lime filler in semi-dense bituminous concrete by Marshall mix design. The characterization studies reported that ceramic dust improves the stability and environmental issues than hydrate lime.…”
Section: Introductionmentioning
confidence: 99%
“…For overall characteristics ceramic dust performs better than lime as a filler and hence satisfy the standards. But from the value of flow for both 3% & 5% ceramic dust filler it's evident that it supports more deformation of surface under traffic load than lime [4].…”
Section: Previous Studiesmentioning
confidence: 95%
“…From the figure its most amount of CCRs waste is produced along with bagasse, coal mining waste, limestone waste, rice wheat saw, nutshell, blast furnace, gypsum, construction waste marble waste, lime slag etc. It is evident that, almost all of these waste materials being used as filler material in experiment and also found satisfactory results [1][2][3][4][5][6][7][8]. And all of these are being produced in a very large amount.…”
Section: Mineral Fillermentioning
confidence: 99%
“…A bituminous concrete mixes with ceramic dust and hydrated lime were prepared in different proportions (3% and 5%) as filler. The stability values and other parameters of samples containing ceramic wastes are improved in comparison to conventional mineral fillers [2]. Using Ceramic waste aggregate 5, 10, 15, 20% replacement of natural aggregate in bituminous macadam pavement.…”
Section: Introductionmentioning
confidence: 99%